THE EFFECT OF WORK DISCIPLINE AND WORK MOTIVATION ON ELEMENTARY SCHOOL TEACHERS' PERFORMANCE IN BLITAR DISTRICT - Achmad Chusairi; Toto Nusantara; Oktaviani Adhi Suciptaningsih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Teacher performance is a major determinant of instructional quality in elementary schools. This study examined the contribution of work discipline and work motivation to elementary school teacher performance in Blitar Regency, both separately and jointly. A quantitative explanatory cross-sectional survey was used. The target population comprised 50 teachers from five public elementary schools, and 38 complete responses were analyzed. Data were collected using three five-item Likert scales measuring work discipline, work motivation, and teacher performance. Multiple linear regression was conducted after tests of validity, reliability, normality, multicollinearity, and heteroscedasticity. All items were valid, and the three scales showed satisfactory reliability (Cronbach's alpha = .821-.867). The regression equation was Y = 4.486 + 0.358X1 + 0.454X2. Work discipline positively predicted teacher performance (B = .358, beta = .329, t = 2.528, p = .016), as did work motivation (B = .454, beta = .505, t = 3.881, p < .001). Jointly, the predictors were significant, F( 2,35) = 14.025, p < .001, explaining 44.5% of the variance in teacher performance (R2 = .445). Work motivation emerged as the relatively stronger predictor. These findings suggest that improving teacher performance requires an integrated strategy that combines a consistent culture of discipline with organizational support for motivation, professional development, recognition, and commitment to student success.